1985
DOI: 10.1007/bf00230899
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ?1tetrahydrocannabinol on luteinizing hormone release in castrated and hypothalamic deafferented male rats

Abstract: delta 1Tetrahydrocannabinol (THC) acutely suppresses tonic serum luteinizing hormone (LH) and prolactin levels in adult male rats. The exact site of its action has not been identified. We have performed complete hypothalamic deafferentation (CHD), which disrupts the medial basal hypothalamus (MBH) from the rest of the CNS, but did not abolish the ability of THC to suppress hypothalamic-pituitary responses in gonadectomized male rats. This was shown by the equal reduction in serum levels of LH and prolactin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The involvement of these receptors in the inhibitory effect of cannabinoids on prolactin secretion has also been described ( 10). Exogenous cannabinoids were effective in the acute suppression of LH and prolactin release in animals after hypothalamic deafferentation ( 15). Recently, we demonstrated that deafferentation did not change CB 1 receptor binding in the hypothalamus ( 16).…”
mentioning
confidence: 99%
“…The involvement of these receptors in the inhibitory effect of cannabinoids on prolactin secretion has also been described ( 10). Exogenous cannabinoids were effective in the acute suppression of LH and prolactin release in animals after hypothalamic deafferentation ( 15). Recently, we demonstrated that deafferentation did not change CB 1 receptor binding in the hypothalamus ( 16).…”
mentioning
confidence: 99%
“…The recent findings that intracerebroventricular THC administration suppresses LH and PRL secretion in the male rat further substantiate a central nervous system site of Received: August 18, 1989 Accepted after revision: March 6, 1990 THC action [12,13]. Although the central site or sites ofTHC action remain to be identified, THC was effective in acutely sup pressing LH and PRL release in hypothalamic-deafferentated animals [2,14]. These data suggest that THC acts locally within the medial basal hypothalamus (MBH) and/or median emi nence (ME) to suppress LH and PRL secretion.…”
mentioning
confidence: 99%
“…In the rat, THC administration reduces LH release in intact [1] and castrated males [2] and recently, was shown to suppress the pulsatile pat tern of LH secretion in castrated testosterone-treated animals [3], Moreover, the tonic circulating level of PRL in the intact male is acutely suppressed following THC administration [4,5], The inhibitory effects ofTHC on LH and PRL secretion appear to result from a central drug action since THC is ineffective in suppressing basal or stimulated LH and PRL release from pitu itary cells in vitro [6][7][8], and since LH-releasing hormone (LHRH) stimulation or administration of exogenous thyrotro pin-releasing hormone readily provokes LH or PRL secretion, respectively, during THC-induced suppression of hormone re lease [9][10][11]. The recent findings that intracerebroventricular THC administration suppresses LH and PRL secretion in the male rat further substantiate a central nervous system site of Received: August 18, 1989 Accepted after revision: March 6, 1990 THC action [12,13].…”
mentioning
confidence: 99%
“…Blockade of CB 1 receptors in this brain region abolished the reduction in plasma PRL levels following Δ 9 -THC administration. CB 1 receptors would be presumably located in neurons intrinsic to the hypothalamus, because Δ 9 -THC was also able to suppress luteinizing hormone (LH) and PRL release in deafferentated animals [16]; furthermore CB 1 receptor binding in hypothalamic nuclei did not change after hypothalamic deafferentation [17]. This agrees with the observation by Mailleux and Vanderhaeghen [15], who found that cell bodies of CB 1 receptor-containing neurons in the hypothalamus are located mainly in the ventromedial nucleus, as revealed by in situ hybridization.…”
Section: Introductionmentioning
confidence: 99%